The Effect of Store Name, Brand Name and Price Discounts on Customer Evaluations and Purchase Intentions in Kathmandu Valley - Aryal, Gaurav (Nepalese Journal of Management, 2025)
The study examines the effect of store name, brand name and price discounts on customer evaluations and purchase intentions in Kathmandu valley. Consumer purchase intention and customer evaluation are dependent variables. The selected independent variables are store name, brand name, price, discount, brand image. The primary source of data is used to assess the opinions of respondents regarding ease of use, security, perceived usefulness, convenience, security, trust, fee charge, consumer satisfaction and consumer spending habits. The study is based on primary data of 111 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of store name, brand name and price discounts on customer evaluations and purchase intentions in Kathmandu Valley. The study showed that brand image has a positive impact on customer evaluation and consumer purchase intention in Kathmandu Valley. It implies that an enhanced brand image leads to increased customer evaluation and consumer purchase intention. The result also showed that price has a negative impact on customer evaluation and consumer purchase intention. It implies that lower the price leads to increased customer evaluation and consumer purchase intention. Moreover, discount has a positive impact on customer evaluation and consumer purchase intention. It implies that greater discount leads to increased customer evaluation and consumer purchase intention. Furthermore, store name has a positive impact on customer evaluation and consumer purchase intention indicating that store name leads to increased customer evaluation and consumer purchase intention. Similarly, the result also showed that brand name has a positive impact on customer evaluation and consumer purchase intention. It indicates that brand name leads to increased customer evaluation and consumer purchase intention.